Nepal’s School Education: Insights of Basic Education in Bagmati Province - Acharya, Bisna; Kharel, Suman; Kharel, Khom Raj (Interdisciplinary Journal of Management and Social Sciences, 2023)
Nepal has made significant progress in school education after 1990s. The government of Nepal has been working towards improving access to school education and enhancing the quality education across the country. Regarding the status of school education, this study has been conducted to examine the present growth trends of school education focusing on basic education in Nepal. For this, descriptive research design has been applied to analyze the data. As per the education policy changes, there has found the significance improvement in net enrolment at basic and primary education, expansion of number of schools and skill development of human resources. The study demands that Nepal needs to bring reality base school education policy for better improving school education quality and provide cent percent school education to all school children.